A CASE OF SPONTANEOUS END-TO-END PERMANENT UNION OF TWO NON HOMOLOGOUS CHROMOSOMES IN THE BRAZILIAN SCORPION TITYUS BAHIENSIS ACCOMPANIED BY IRREGULARITIES IN PAIRING - Piza Jor., S. de Toledo (REVISTA DE AGRICULTURA, 2015)
A CASE OF SPONTANEOUS END-TO-END PERMANENT UNION OF TWO NON HOMOLOGOUS CHROMOSOMES IN THE BRAZILIAN SCORPION TITYUS BAHIENSIS ACCOMPANIED BY IRREGULARITIES IN PAIRING